(untitled) (Revista da Faculdade de Medicina Veterinária, Universidade de São Paulo, 1971)
The author present the result of the qualitative chemical composition of the urinary calculy in the canine species. The observations are referring to 85 urinary calculy obtained from animals attended at the ambulatory of the surgical clinic of the Faculty of Veterinary Medicine of São Paulo’s University. Those animals were of different sexes, races, sizes and of age varying between 2 and 16 years. After verifying the lack of studies referring to the chemical composition of urinary calculy of dogs in Brazil, the author present bibliographical review about this matter as well as the technical analysis used. He compares the results obtained with those from foreign authors and comes to the following clues: 1 — The calculy compound of phosphates are the most commons. The percentage is 65,8% of magnesium ammonium phosphate (triple phosphate), and 35,2% of calcium and magnesium phosphate (amorphus phosphate). 2 — Follow in frequence the calculy compound of oxalates in the proportion of 45,8%, greater as the mentioned by other authors. 3 — The presence of cholesterol in the analysis of urinary calculy of the dogs, 29,5%, is very different from the observation made by other authors which, except one, do not mentioned it. 4 — The fibrine, element not mentioned by the authors was observed in 34,1% of the calculy. 5 — Cystine, uric acid and urates are observed by authors relatively often, but were not present in the calculy studied by us.